DEVELOPMENT OF VOCABULARY - METHODOLOGICAL BASIS OF FORMING SPEECH COMPETENCE: FROM THE EXPERIENCE OF TEACHING THE MOTHER LANGUAGE - Nilufaroy Ahmadjonova (International Journal of Literature and Language Studies, 2026)
This article scientifically and methodologically analyzes the role and importance of lexical wealth in the formation of students' speech competence in the process of teaching the mother tongue. Methodological approaches and a system of practical exercises aimed at developing oral and written speech competence based on systematic work with explanatory, spelling and orthoepic dictionaries are considered. In addition, scientific and practical recommendations have been developed on ways to consistently expand students' vocabulary through the integrated use of interactive, creative and multimedia tools.